ANALYSIS OF THE REASONING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING GEOMETRY PROBLEMS IN BUILDING SPACE - Mehrbakhsh Nilsashi; Rizli Ansyari (Universitas Labuhanbatu, 2023)
This research aims to find out how much the level of reasoning ability of female students in solving problems on the material of geometry build space, because reasoning is one of the standards that are needed in learning mathematics and become one of the objectives of learning mathematics and is needed for problem solving in everyday life. This type of research is a descriptive qualitative approach. The sample of this research is 30 students of class VIII A SMPs METHODIST 1 RANTAUPRAPAT with the research method is a written test. From this study shows that the level of reasoning ability of high students is only 27%, while students who have a moderate level of reasoning ability by 53% and students who have a low level of reasoning ability by 20%.